Identification Customer Needs of Shuttle Travel by Using Servqual and Kano Methods - Syeren Anastasya; Sari Wulandari; Agus Achmad Suhendra (International Journal of Innovation in Enterprise System, 2023)
Bhinneka Shuttle is a companies which is engaged in customer delivery transportation services and was founded in 1972. Throughout 2022, Bhinneka Shuttle experienced an unstable amount of revenue and did not achieve the target number of passengers. Based on the results of a comparison of the four branches of Bhinneka Shuttle outlets in Bandung City, it is known that Bhinneka Shuttle Mekar Wangi needs to get improvement priority. This is supported by the low Google review rating and many complaints about the performance of the services provided. Customer dissatisfaction and high competition in the transportation business require Bhinneka Shuttle Mekar Wangi to improve and increase the quality of its services. This study aims to identify True Customer Needs by using the integration of the Servqual method and the Kano Model so that priority attributes are obtained for improvement and become basic recommendations for designing company service quality improvements. The attribute needs were obtained by conducting a study of the literature and Voice of Customer which were classified into five Servqual dimensions, that is Reliability, Comfort, Extent of Service, Safety, and Affordability (RESCA). According to research result, 11 attributes True Customer Needs that needed to be improved which states that the services provided by Bhinneka Shuttle still does not provide satisfaction to consumers. Bhinneka Shuttle are suggested to pay more attention to weak attributes that are included in the must be category because they are basic need in company’s services.